Digital Life Together : the challenge of technology for Christian schools - Smith, David I., 1966- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2020)
"Walks educators, leaders, and parents through some of the big ideas that are hidden in our technology habits. The book draws from interviews, surveys, classroom observations, and school records to examine the impact of technology on Christian learning"--
Includes bibliographical references and index.
Keywords: Educational technology; Technology -- Religious aspects -- Christianity; Church schools